Perancangan Sistem Informasi Penjualan pada PT. Jaco Indosehat Sempurna Cabang Banda Aceh - Mahmudi; Ismail; Imilda (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2024)
The development of information technology has changed the paradigm in seeking and sharing information, including in the world of commerce. E-commerce is one of the important innovations that changes transaction patterns to become easier and more efficient. The focus of this research is the design of an information system for selling household products at PT. Jaco Perfect Indosehat Banda Aceh Branch. The waterfall method is used in system development, including requirements analysis, design, implementation, testing and maintenance. The results of system design include input, output, process, control, labor and cost designs. The designed application has features such as Login Form, Main Menu, Item Input, Sales Input, Item List, and View Sales Transaction List. The conclusion shows that this system has the potential to increase the efficiency of sales data management. The suggestions put forward are to increase optimal use of computers, add quality brainware, and increase skills in using information technology. It is hoped that PT. Jaco Indosehat Perfect Banda Aceh Branch can utilize this system optimally to achieve its business goals.